Instructions emphasizing velocity, accuracy or both in performance and kinematics of overarm throwing by experienced team handball players - van den Tillaar, R.; Ettema, G. (Perceptual and Motor Skills, 2003)
On motor tasks like the overarm throw, velocity and accuracy are two important parameters of performance that may be incompatible and require different strategies in the execution of the motor task. The purpose was to investigate the effects of instruction (emphasizing velocity, accuracy, or both) on performance and kinematics of overarm throwing. Results for 9 experienced male team handball players (M age=24 ± 2.2 yr.) showed type of instruction affected the maximal ball velocity. The difference in ball velocity reflected the significant difference in maximal linear velocity of the wrist, elbow, and hip segments together with their absolute timing before ball release. The subjects did not seem to change their throwing technique, i.e., the relative timing of movement initiation of the different body segments.